Atypical neural processing of rise time by adults with dyslexia. (April 2019) - Van Hirtum, Tilde; Ghesquière, Pol; Wouters, Jan
Abstract: In recent studies phonological deficits in dyslexia are related to a deficit in the synchronization of neural oscillations to the dynamics of the speech envelope. The temporal features of both amplitude modulations and rise times characterize the speech envelope. Previous studies uncovered the inefficiency of the dyslexic brain to follow different amplitude modulations in speech. However, it remains to be investigated how the envelope's rise time mediates this neural processing. In this study we examined neural synchronization in students with and without dyslexia using auditory steady-state responses at theta, alpha, beta and low-gamma range oscillations (i.e., 4, 10, 20 and 40 Hz) to stimuli with different envelope rise times. Our results revealed reduced neural synchronization in the alpha, beta and low-gamma frequency ranges in dyslexia. Moreover, atypical neural synchronization was modulated by rise time for alpha and beta oscillations, showing that deficits found at 10 and 20 Hz were only evident when the envelope's rise time was significantly shortened. This impaired tracking of rise time cues may very well lead to the speech and phonological processing difficulties observed in dyslexia.